Perioral dermatitis due to lip-licking. - Jansen, T.; Bader, A.; Altmeyer, P. (European Journal of Pediatric Dermatology, 2000)
Perioral dermatitis is a relatively uncommon condition in children. A case of perioral rash due to lip-licking in a 10-year-old girl is reported. Parents usually do not notice the lip-licking and may be unaware that it might be the cause of skin irritation in their children.